Hubungan Kadar Kesadahan dan Fluorida dalam Air Bersih pada Kejadian Penyakit Periodontal di Kecamatan Pundong, Kabupaten Bantul, Yogyakarta - Bekti Nur'aini; Prayudha Benni Setiawan; Rieski Prihastuti; Budi Rodestawati; Christia Aye Waindy Vega (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2023)
Latar belakang: Penyakit periodontal termasuk masalah kesehatan oral di Indonesia dengan jumlah kasus periodontitis sebesar 74,10% pada tahun 2018. Penyakit periodontal pada tingkat keparahan tinggi dapat menyebabkan kehilangan gigi. Faktor primer penyebab penyakit periodontal adalah plak gigi dan diperkuat oleh keberadaan kalkulus. Terjadinya pembentukan kalkulus dapat meningkat bersama dengan jumlah kalsium dan mineral lainnya dalam saliva termasuk fluorida. Air sumur sebagai sumber air bersih yang digunakan masyarakat mengandung kesadahan dan fluorida. Tujuan penelitian ini adalah untuk mengetahui hubungan kadar kesadahan dan fluorida dalam air bersih pada kejadian penyakit periodontal di Kecamatan Pundong, Kabupaten Bantul, Yogyakarta.Metode: Penelitian ini adalah penelitian observasional analitik dengan desain case control (kasus kontrol). Subjek penelitian sebanyak 120 responden, 60 kasus terdiagnosis penyakit periodontal dan 60 kontrol tidak terdiagnosis penyakit periodontal. Penelitian ini menggunakan data primer berupa sampel air bersih yang diujikan di Balai Laboratorium Kesehatan Yogyakarta, data sekunder berupa data penyakit periodontal dari rekam medis pasien Puskesmas Pundong, Kecamatan Pundong, Kabupaten Bantul Yogyakarta pada tahun 2016. Variabel bebas adalah kadar kesadahan dan fluorida dalam air bersih, variabel terikat adalah penyakit periodontal. Data yang diperoleh diuji menggunakan bivariate Chi Square dengan tingkat signifikansi 0,05 (5%).Hasil: Berdasarkan analisis bivariate, variabel kesadahan tidak berhubungan dengan kejadian penyakit periodontal (p=0,3153; OR=1,16), begitu pula variabel kadar fluorida tidak berhubungan dengan kejadian penyakit periodontal (p=0,1664; OR=1,7).Simpulan: Kadar kesadahan dan fluorida dalam air bersih tidak memiliki hubungan yang signifikan dengan kejadian penyakit periodontal. ABSTRACT Title: Relationship between Hardness and Fluoride Levels in Water with Incidence of Periodontal Disease in Pundong District, Bantul Regency, YogyakartaBackground: Periodontal disease is one of oral health problems in Indonesia with 74.10% of periodontitis cases in 2018. Periodontal disease at high levels of severity can cause tooth loss. The primary factor causing periodontal disease is dental plaque and reinforced by the presence of calculus. The occurrence of calculus formation can increase along with the amount of calcium and other minerals in saliva including fluoride. Well water as a source of clean water used by the community contains hardness and fluoride. The purpose of this study was to determine the relationship between hardness and fluoride levels in water on the incidence of periodontal disease in Pundong District, Bantul Regency, Yogyakarta.Method: This research was analytical observational study with a case control design. The research subjects were 120 respondents, consisting of 60 cases with diagnosis of periodontal disease and 60 controls without diagnosis of periodontal disease. This study used primary data in the form of water samples tested at the Yogyakarta Health Laboratory Center, secondary data in the form of periodontal disease data from medical records of patients at the Puskesmas Kecamatan Pundong, Pundong District, Bantul Regency, Yogyakarta in 2016. The independent variables were fluoride and hardness levels in water, the dependent variable was periodontal disease. The data obtained was tested using Chi Square bivariate with a significance level of 0.05 (5%).Result: Based on bivariate analysis, the hardness variable was not associated with the incidence of periodontal disease (p=0.3153; OR=1.16), as well as the fluoride level variable was not associated with the incidence of periodontal disease (p=0.1664; OR=1, 7).Conclusion: Hardness and fluoride levels in water have no significant relationship with the incidence of periodontal disease.